Kidney Involvement in PSTPIP1 Associated Inflammatory Diseases (PAID): A Case Report and Review of the Literature - Borgia, Paola; Papa, Riccardo; D'Alessandro, Matteo; Caorsi, Roberta; Piaggio, Giorgio; Angeletti, Andrea; Ceccherini, Isabella; Ghiggeri, Gian Marco; Gattorno, Marco (Frontiers in Medicine, 2021)
The pyogenic arthritis, pyoderma gangrenosum and acne (PAPA) syndrome and the PSTPIP1-associated myeloid-related proteinemia inflammatory (PAMI) syndrome are two rare autoinflammatory disorders caused by heterozygous mutations of the PSTPIP1 gene. They are characterized by skin and joint involvement, and hepato-splenomegaly, pancytopenia, and growth failure in the case of PAMI syndrome. Kidney involvement has been rarely reported. Only two missense variants of the PSTPIP1 gene (p.E250K and p.E257K) have been associated with PAMI syndrome. Long-term treatment with interleukin (IL)-1 inhibitors is effective to control inflammatory manifestations and usually well tolerated. We report a case of a patient carrying the PSTPIP1 p.E250K mutation who developed a late-onset kidney involvement despite a long treatment with canakinumab and anakinra. Kidney biopsy showed focal segmental glomerulosclerosis that was treated with tacrolimus (0.1 mg/Kg/day in 2 doses). After 5 months, due to the worsening of skin manifestations, tacrolimus was discontinued and canakinumab restarted resulting in a prompt skin benefit. A literature revision with the aim to assess the proportion and type of kidney involvement in PAMI syndrome revealed that heterogeneous nephropathies may be part of the clinical spectrum. Our study reinforces the importance of a periodic diagnostic work-up, including kidney laboratory tests and kidney biopsy, in individuals affected with PAMI syndrome. Kidney and liver functions may be impaired regardless anti-cytokines treatments and additional therapy approaches (i.e., multi-drugs, hematopoietic stem cell transplantation) should be carefully considered.